Preoperative nutritional status impacts clinical outcome and hospital length of stay in pelvic exenteration patients – a retrospective study. Issue 1 (March 2022) - Hogan, Sophie; Steffens, Daniel; Vuong, Kenneth; Rangan, Anna; Solomon, Michael; Carey, Sharon
Background: Preoperative malnutrition is common in surgical oncology patients and can have negative effects on postoperative outcomes. Pelvic exenteration is major surgery associated with high morbidity rates. Associations between preoperative malnutrition, determined using the patient-generated subjective global assessment, and postoperative outcomes in this patient cohort has not yet been investigated. Aim: To determine if preoperative nutritional status is associated with postoperative surgical and quality of life (QoL) outcomes after pelvic exenteration surgery. Methods: A retrospective cohort study was conducted at a quaternary hospital investigating 123 patients who had pelvic exenteration surgery from January 2017 to August 2019. Preoperative nutritional status and postoperative surgical and QoL outcomes were collected and analysed to determine any associations. Results: Overall, 49.6% of patients were female with a median age of 59 years. Forty patients (32.5%) were malnourished and 83 (67.5%) were well nourished before surgery. Well-nourished patients had a shorter length of hospital stay ( p = 0.034) and at 6 months post-surgery, presented with a significantly better physical and mental QoL score ( p = 0.038 and p = 0.001 respectively). The regression analyses showed that intensive care unit (ICU) readmission rates were 7.19 times more likely to occur in malnourished patients ( p = 0.022). Conclusions: Preoperative malnutrition is associated with increased length of stay, ICU readmissions and poorer QoL following pelvic exenteration. Nutrition screening, assessment and optimisation of management are essential in this patient cohort to improve patient outcomes. Future studies are needed to measure the effect of interventions and identify the most beneficial model of care for this complex patient group.